Thirdhand Smoke Exposure Ignored by Pediatricians: A Cross-sectional Study - Gizem Özcan; Emine Kaygı Tartıcı; Binnaz Çelik (Turkish Archives of Pediatrics)
Objective: Thirdhand smoke (THS) is defined as the harmful substances in cigarette smoke that are absorbed into objects, people, and surfaces after smoking. This study aimed to determine the level of awareness of pediatricians working in a tertiary healthcare institution about THS exposure.